2007
DOI: 10.1145/1210268.1210274
|View full text |Cite
|
Sign up to set email alerts
|

The Molen compiler for reconfigurable processors

Abstract: In this paper, we describe the compiler developed to target the Molen reconfigurable processor and programming paradigm. The compiler automatically generates optimized binary code for C applications, based on pragma annotation of the code executed on the reconfigurable hardware. For the IBM PowerPC 405 processor included in the Virtex II Pro platform FPGA, we implemented code generation, register, and stack frame allocation following the PowerPC EABI (embedded application binary interface). The PowerPC backend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 5 publications
0
19
0
5
Order By: Relevance
“…FPGA-based reconfigurable architecture has been used in cooperation with ad-hoc, or extended version of standard compiler to create runtime adaptable system, as presented in [11,12]. These approaches take advantages by the use of the compiler optimization to create the supposed to be, best configuration for a given application.…”
Section: Related Workmentioning
confidence: 99%
“…FPGA-based reconfigurable architecture has been used in cooperation with ad-hoc, or extended version of standard compiler to create runtime adaptable system, as presented in [11,12]. These approaches take advantages by the use of the compiler optimization to create the supposed to be, best configuration for a given application.…”
Section: Related Workmentioning
confidence: 99%
“…However, one of the existing drawbacks of this framework is the lack of available support for a high abstraction level design methodology, in order to reduce design complexity. Additionally, works such as Molen (Panainte et al 2007) propose efficient compilers for reconfigurable architectures. The proposed Molen compiler was implemented on a Virtex II FPGA, and takes into account details such as related to synthesis placement conflicts as well as reconfiguration latencies.…”
Section: Targeting Coarse Grain Architecturesmentioning
confidence: 99%
“…Additionally the compiler plug-in must be modified to insert a call to this set instruction before any call to the execute instruction. A simplistic method to achieve this would be to simply insert the set instruction before the execute instruction, but [27] has already shown that better performance can be gained by inserting the call at earlier times. The methods described there can easily be applied to the compiler plug-in, or the other way around.…”
Section: Partial Reconfigurationmentioning
confidence: 99%